(untitled) (Baghdad Science Journal, 2019)
Molecular farming has become one of the most significant implementations of modern biotechnology to generate modified plant crops to produce medicinal proteins. Agrobacterium is one plant genetic engineering tool that integrates genes of interest inside a host plant. In recent years, the need to produce recombinant proteins as therapeutics has growing rapidly, and human glucocerebrosidase is one of the proteins that is need to treat disease. In this study, specific primers were designed to amplify Hu-GBA1 gene from constructed pGEM-GBA plasmid which was cloned into the plant expression vector pCAMBIA1304. The generated recombinant pCAMBIA1304-GBA plasmid was used to transform A. tumefaciens LBA4404 and applied for transformation of sunflower cotyledon explants. Colony PCR technique was used to confirm the presence of Hu-GBA1 gene in transformed A. tumefaciens. Agrobacterium containing pCAMBIA1304-GBA was suspended in Infection Medium (IM) supplement with 200 mM acetosyringone. A bacterial suspension was used to transform sunflower cotyledons. After infection, cotyledons were co-cultivated in Co-cultivation medium (CCM), supplied with 200 mM acetosyringone without antibiotics. The cotyledons were then transferred to selection media containing 7.5 mg/L Hygromycin and 250 mg/L Cefotaxime and grown for additional 14 days at 25℃ in photoperiod of 16h L/8h D. The transformed sunflower cotyledons were successfully generated complete plant with used 6-Benzylaminopurine and Naphthalene acetic acid as growth hormones. The presence of the Hu-GBA1 gene in the genomic DNA of transgenic sunflower plant was proven by PCR as a band of 1561bp size. The GBA mRNA expression in modified sunflowers was detected by qRT-PCR compared with control GBA mRNA. Enzyme Linked Immunoassay was done on crude recombinant protein that extracted from transformed sunflower using Human Glucosylceramide ELISA Kit, the Elisa test results confirmed the production of recombinant glucocerebrosidase and the concentration of crude recombinant enzyme extracted from transformed sunflower with GBA1 gene was 0.45 ng/µl